2017
DOI: 10.1016/j.breast.2016.12.017
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of eribulin as first- to third-line treatment in patients with advanced or metastatic breast cancer previously treated with anthracyclines and taxanes

Abstract: Eribulin exhibited efficacy and manageable tolerability in Japanese women with pretreated MBC in first- to third-line use. (ID: UMIN000007121).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
19
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 26 publications
(35 reference statements)
6
19
3
Order By: Relevance
“…The incidence of febrile neutropenia in EMBRACE (5%) was higher than that of the Kaufman study (2%), which was attributed to more prior lines of chemotherapy (up to 5) in EMBRACE. In our study, in which eribulin was exclusively used as third line, the incidence was also 5%, similar to a recent Japanese study, in which eribulin was used as first line treatment in 48.9% of the patients, as second in 29.8% and as third in 21.3% and the incidence of febrile neutropenia was 8.5%; thus, it seems that the line of therapy has little to do with reported febrile neutropenia.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The incidence of febrile neutropenia in EMBRACE (5%) was higher than that of the Kaufman study (2%), which was attributed to more prior lines of chemotherapy (up to 5) in EMBRACE. In our study, in which eribulin was exclusively used as third line, the incidence was also 5%, similar to a recent Japanese study, in which eribulin was used as first line treatment in 48.9% of the patients, as second in 29.8% and as third in 21.3% and the incidence of febrile neutropenia was 8.5%; thus, it seems that the line of therapy has little to do with reported febrile neutropenia.…”
Section: Discussionsupporting
confidence: 89%
“…It has been reported that eribulin shows better OS results at third line than at later lines of treatment, and this might also apply when comparing earlier lines of treatment (the Kauffman study, 50.5% in second line), to third line. In the Japanese study, with almost 50% of the patients in first line, the median OS was even larger at 17.4 months, which further suggests that OS gets larger when eribulin is used in earlier lines of treatment. In that study, median OS in patients treated in first line was not reached while it was 11.8 months in second/third line.…”
Section: Discussionmentioning
confidence: 92%
“…We postulate that the risk of FN in Japanese patients may tend to be higher. However, the incidence of FN was 8.5% in a phase II study in Japanese patients who had received from one to three lines of eribulin therapy . With regard to non‐hematological AEs, PN occurred in 21 (72.4%) patients, at grade 3 in only four (13.8%); however, all AEs occurred during pretreatment, not during eribulin therapy.…”
Section: Discussionmentioning
confidence: 99%
“…However, the disease often progresses due to primary or acquired resistance to these treatment regimens, and there are few subsequent therapeutic options for patients with refractory disease . Over the past several years, eribulin mesilate, a microtubule inhibitor, has shown reasonable efficacy with acceptable toxicity in patients with RBC/MBC . The phase III EMBRACE trial of eribulin mesilate for women with pretreated metastatic breast cancer showed promising results, showing a significant improvement in median overall survival of 2.5 months compared with the treatment of physician's choice …”
Section: Introductionmentioning
confidence: 99%